Assessing vulnerability and community knowledge of climate change impacts on Bawean Island, Indonesia - Mubarok, Mohammad Fahmi; Sawiji, Asri; Perdanawati , Rizqi Abdi (Journal of Marine Resources and Coastal Management, 2024)
Bawean Island, located in Gresik Regency, is highly vulnerable to the impacts of climate change due to its coastal position. One of the significant impacts is sea level rise, which increases the risk of tidal floods. Effective and timely decision-making is essential to mitigate and manage these risks. This study focuses on mapping vulnerability and assessing the level of community knowledge regarding climate change to evaluate the island's susceptibility. The objectives include identifying data, measuring community knowledge levels, and analyzing vulnerability. The findings reveal that 323 hectares fall into the vulnerable category, while 1 hectare is classified as very vulnerable. The community's knowledge level is predominantly high, with 73% of respondents scoring high and 27% moderate. Inundation predictions for the next 20 years, based on a sea level rise of 3 cm per year, estimate an inundation area of 319,398 hectares in 2024 with a sea level rise of 2.64 cm. By 2044, the highest high-water level (HHWL) of 4.00 cm could inundate an area of 442,625 hectares. These findings underscore the urgent need for adaptation strategies to mitigate the risks of tidal floods and enhance the resilience of coastal communities on Bawean Island.